Pengaruh Destination Image dan Travel Experience terhadap Revisit Intention dengan Tourist Satisfaction Sebagai Variabel Mediasi pada Wisatawan Domestik di Lawang Sewu Semarang - Lisna Monica; Bahrain Pasha Irawan (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the influence of Destination Image and Travel Experience on Revisit Intention, with Tourist Satisfaction as a mediating variabel among domestic tourist visiting Lawang Sewu in Semarang. A quantitative approach was applied using 150 respondents, and the data were processed using Partial Least Squares Structural Equation Modeling ( PLS-SEM). The findings indicate that both Destination Image and Travel Experience have a positive and sifnificant effect on Tourist Satisfaction. Furthermore, Tourist Satisfaction significantly influences Revisit Intention. The result also reveal that Tourist Satisfaction server as a significant mediating variabel in the relationship between Destination Image and Travel Experience with Revisit Intention. This suggests that a positive Destination Image and memorable Travel Experience s enhance Tourist Satisfaction, which subsequently increases their intention to Revisit Intention. These result highlight the importance for heritage destination managers to strengthen destination image, improve visitor experiences, and enhance servise quality to foster tourist loyalty and support sustainable tourism development. Keywords: destination image, mediating effect, tourist satisfaction, travel experience , revisit intention.